You're only as good as your next one 100 great films, 100 good films, and 100 for which i should be shot - Medavoy, Mike; Young, Josh (Pocket books, 2002)
A Hollywood insider provides a personal history of the movie industry, describing his rise from the Universal Studios mailroom to become head of Phoenix Pictures and his many successes and failures along the way.
Keywords: Medavoy, Mike; Motion picture producers and directors -- United States -- Biography; Filmproduzent; Filmregisseur; USA; Biografie; Autobiografie